Hubungan Tingkat Pengetahuan Ibu Tentang Pencegahan Dan Pengobatan Diare Dengan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Margai - Yuniantari, Ni Wayan; Septiari, I Gusti Ayu Agung; Tunas, I Ketut (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2024)
Diarrhoea is a disease that can occur in all age groups, the most vulnevable group to this disease is toddlers. Diarrhea is defined as the condition of loose or liquid bowel movements three or more times per day (or more often than normal for individuals). Based on data from the Central Statistics Agency (BPS) for Bali Province in 2019, Tabanan Regency is the district with highest of diarrhea with the total of 10,225 cases, then in 2020 cases in Tabanan Regency decreased to 8,074 cases, but Tabanan Regency is still the third Regency with the highest number of diarrhea cases in Bali Province. This study aims to determine the relationship between the level of knowledge of mothers about the prevention and treatment of diarrhea with the incidence of diarrhea in toddlers in the working area of ​​the Marga I Health Center. This study used a quantitative observational research design with an approach Cross-Sectional with 100 randomly selected samples Two Stage Random Sampling. The variables studied were mother's knowledge as the independent variable and the incidence of diarrhea in toddlers as the dependent variable. The instrument used is a questionnaire that has been tested for validity and reliability. Data were analyzed by test Chi-Square using SPSS. The results showed that the majority of mothers had a good level of knowledge (48%) as many as 13% had diarrhea. Mothers with a moderate level of knowledge (31%) as much as 10% experienced diarrhea. In mothers with a low level of knowledge (21%) as many as 13% experienced diarrhea. Test results Chi-Square in this study obtained valuep-value = 0.019 (p<0.05). Based on the results of the study, there is a relationship between the mother's level of knowledge about the prevention and treatment of diarrhea and the incidence of diarrhea in toddlers in the working area of ​​the Marga I Health Center. It is recommended that education be carried out regarding the prevention and treatment of diarrhea.